PENYULUHAN NUTRISI SEIMBANG UNTUK PENCEGAHAN STUNTING PADA ANAK DI BANJAR JAGATAMU, DESA MELILING, TABANAN - I Gusti Ayu Prema Yani Sideme; Ida Ayu Mirah Agung; I Made Benni Labba P. (Bajang Institute, 2025)
Stunting is still one of the unresolved child health problems in Indonesia. Education related to providing balanced nutrition is one of the critical keys to preventing stunting in children. We conducted a pediatric health education program regarding